2016
DOI: 10.9789/2175-5361.2016.v8i2.4423-4434
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco para lesão de córnea em pacientes criticos na terapia intensiva: uma revisão integrativa Risk factors for injury in the cornea in critical patients in intensive care: an integrative review

Abstract: Oliveira RS, Fernandes APNL, Botarelli FR et al. Objective: summarizing the scientific content produced about the risk factors for corneal injury in critically ill patients in intensive care. Method: this is an integrative review of the literature conducted by question: "Which risk factors are involved in the development of corneal injury in critically ill patients in intensive care?" We searched the banks of BDENF, LILACS, SciELO and MEDLINE. The collection was performed according to the research protocol fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
(19 reference statements)
0
2
0
1
Order By: Relevance
“…Intensive care patients have a great possibility of developing adverse eye changes due to mechanical ventilation, and the use of medications, such as muscle blocking drugs, sedatives and diuretics that interfere with the cornea's protective mechanisms, interfering with effective eyelid closure and the production of tears. (35) According to the findings of the current study, less than half of the participant patients in both groups were between (50-60) years old. This could be explained by the fact that the majority of eye diseases are considered to be age-related disease because the prevalence of the eye diseases rises with age.…”
Section: Discussionmentioning
confidence: 68%
“…Intensive care patients have a great possibility of developing adverse eye changes due to mechanical ventilation, and the use of medications, such as muscle blocking drugs, sedatives and diuretics that interfere with the cornea's protective mechanisms, interfering with effective eyelid closure and the production of tears. (35) According to the findings of the current study, less than half of the participant patients in both groups were between (50-60) years old. This could be explained by the fact that the majority of eye diseases are considered to be age-related disease because the prevalence of the eye diseases rises with age.…”
Section: Discussionmentioning
confidence: 68%
“…A dinâmica do ambiente da terapia intensiva pode levar a priorização de cuidados específicos, imediatos e complexos ao paciente crítico, em decorrência de outros cuidados básicos, porém essenciais. (1) Quando a gravidade não gera risco iminente à vida, os cuidados podem ocorrer com menor frequência ou não serem evidenciados, podendo ser até suprimidos, como é o caso do cuidado com os olhos do paciente crítico.…”
Section: Introductionunclassified
“…[1][2][3][4] Lagophthalmos (the inability to close the eyelids completely), mechanical ventilation (MV) therapy, impaired consciousness, use of paralytics, and longer duration of hospitalization are the main causative factors of EK in patients treated in intensive care units (ICUs). 1,[5][6][7] The rate of EK in ICU patients under MV was reported in previous studies to be between 2% and 57%. 3,[8][9][10] In an earlier phase of this study, the rate of EK was found to be 2%.…”
Section: Introductionmentioning
confidence: 99%